PENGEMBANGAN BOOKLET SEJARAH PEREKONOMIAN LOKAL UNTUK MAHASISWA PENDIDIKAN SEJARAH - Najuah - -; Abdul Haris Nasution (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2017)
The challenge of the beginning of the econmy local history development. Interest Study of econmoy Local history in the colonial. The background of this research is necessary the developing of the history material lesson with local economy history material in the colonial. Because of lack of material in accordance with KKNI 2013 Curiculum. The characteristic of the targets and the needs of studnts and some relics of the local history in East Sumatra in the colonial underutilized in learning history. Plug Scientific and Technological progress more sophisticated so that students lazy to seek and read the history books. For it, the researchers developed history material lesson used RnD method (Research and Development) that is research used to product certain products and test products effectivenese. Purpose of this research are : (1) describe material lesson that during this time used in history about economy local history in the colonial in East Sumatra for student at third semester in JPS FIS Unimed, (2) product mateial lesson according to the needs of the history learning especially economy local history substance for students, (3) knowledge and analyzed effectivenese of material lesson that developed in economy local hisory learning about interest study for students. The result of research howing (1) the developed of material lesson shaped economy local history substance in colonial (2) students more understanding with economy local history in colonial, students activity involved in laerning-teaching process and more motivated and easy to understand history lesson, interest study and curiousity of students more high, and (3) the booklet effectivenese give the positive influence to interest study. The conclusion of this research are (1) the developing of history lesson material through two steps testing by expert team (2) application of history lesson material can make students more interest to study history, brave argued opinion, active in learning process and respect for opinions other people, (3) application of developing of history lesson material has did by research give the positive influence for interest study of students. Based on same of the above conclusions, researcher ask the suggestion as here. The teacher should start to develop materials in accordance with the curiculum, the good lesson material should comply all effective, efficient and innovative criteria and following the development of science nad technology. Keywords : history lesson material, bookled, economy local history.